Stabilization of Magnetic Skyrmions on Arrays of Self-Assembled Hexagonal Nanodomes for Magnetic Recording Applications - Oyarzun-Medina, S; Palma-Solorza, J; Tejo-Lazo, F; Casagrande-Denardin, J; Hermosilla-Avila, J (American Chemical Society, 2020)
Magnetic skyrmions are nontrivial spin textures that resist external perturbations, being promising candidates for the next-generation recording devices. Nevertheless, a major challenge in realizing skyrmion-based devices is the stabilization of ordered arrays of these spin textures under ambient conditions and zero applied field. Here, we demonstrate for the first time the formation and stabilization of magnetic skyrmions on the arrays of self-assembled hexagonal nanodomes taking advantage of the intrinsic properties of its curved geometry. Magnetic force microscopy images from the arrays of 100 nm nanodomes showed stable skyrmions at the zero field that are arranged following the topography of the nanostructure. Micromagnetic simulations are compared to the experiments to determine the correlation of the domain textures with the topography of the samples. We propose a simple method to nucleate and annihilate skyrmions, opening the possibility for an ultradense data storage based on the high stability and low energy consumption of the skyrmionic textures. © 2020 American Chemical Society.